2015
DOI: 10.1007/s10389-015-0684-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the psychosocial work environment of professional drivers

Abstract: Aim Along with globalization in recent periods, psychosocial risks at the workplace have been classified as considerable developing risks for human mental and physical health. These risks exist both in developed and developing countries. The current study aims to assess the psychosocial work environment of professional drivers in a multidimensional concept. Subject and methods The study population consisted of 645 Iranian professional drivers. Psychosocial factors were examined in five domains including job de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The operational employees showed higher occupational demands, especially in sensory and cognitive scales, which agreed with the results obtained in a study in Portugal (on a small sample size and using the short version of COPSOQ) [38] . In a domestic study conducted on professional drivers in 2014, occupational demand was high in sensory and cognitive scales [33] . The high level of occupational demand in operational electricity employees indicates high job sensitivity of employees and sensory and subjective needs including good eyesight and high concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operational employees showed higher occupational demands, especially in sensory and cognitive scales, which agreed with the results obtained in a study in Portugal (on a small sample size and using the short version of COPSOQ) [38] . In a domestic study conducted on professional drivers in 2014, occupational demand was high in sensory and cognitive scales [33] . The high level of occupational demand in operational electricity employees indicates high job sensitivity of employees and sensory and subjective needs including good eyesight and high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in scores from 0 to 500 for job demand and job content domains with five scales, 0–800 for interpersonal relationships and leadership domain with eight scales, 0–200 for person−work interface with two scales and 0–600 for the health and well being domain with six scales. A higher score indicates more unfavorable psychosocial conditions in the workplace [ 18 , 33 , 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, numerous research studies also indicated that psychosocial work factors such as fatigue, stress and driving styles of the bus drivers are also important factors for aggressive driving behaviours. In particular, poor psychosocial work environment in job demand, job content, work-individual interface as well as having a car accident history were found to be associated with poor level of health and well-being and more stress symptoms (Aminian, et al, 2015). Another study also found that over 95% of urban bus drivers working for more than 10 hours per day would present fatigue factors related to perceptions of demands at work and exposure to environmental stressors.…”
Section: Comparison With Other Bus Driving Cyclesmentioning
confidence: 94%